TRANSFORMASI NOVEL GERBANG DIALOG DANUR KARYA RISA SARASWATI KE DALAM FILM DANUR: I CAN SEE GHOST KARYA AWI SURYADI (KAJIAN EKRANISASI) - Nurislamiah, Nurislamiah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2020)
This study purpose to describe the forms of ekranisasi that shrinkage, addition, and variation changes in intrinsic elements of plot, character, and setting. The research method used is descriptive qualitative. The results of this study indicate that the most common form of ekranisasi is shrinkage and addition resulting in significant differences between novels and films. The conclusion in this study is that the ekranisasi procces occurs because there are elements that are unimportant to visualize, consideration of duration, and consideration of commercial aspects.